KETERBATASAN AKSES DAN INFRASTRUKTUR DALAM KEBERLANGSUNGAN PENDIDIKAN VOKASIONAL - Prasetyo Ady Nugroho Putra (ADISAM PUBLISHER, 2026)
The limited access and infrastructure faced by vocational education institutions in disadvantaged areas have posed significant challenges in the implementation of effective learning media strategies. The lack of information and communication technology facilities, such as computers, internet networks and other digital devices, limits the use of modern learning media that are interactive and engaging. In addition, the scarcity of teachers who are competent and capable of effectively using innovative learning media exacerbates the situation. As a result, conventional teaching methods that lack student participation are still widely used, slowing down the transfer of skills and knowledge needed in the job market. Ineffective learning media strategies have the potential to reduce the quality of graduates and weaken the competitiveness of the vocational workforce in the digital era.